IMPLEMENTASI TPACK DENGAN MEMANFAATKAN APLIKASI KAHOOT SEBAGAI MEDIA PEMBELAJARAN BERBASIS DIGITAL GAME BASED LEARNING DI SD - Ade Isamiati; Darmansyah Nabar (Cerdas Proklamator, 2023)
One way that we can use to implement TPACK learning in schools is by using the Kahoot application. The use of the Kahoot application is able to increase effectiveness in learning because teachers and students interact with each other in learning through games, polls or quizzes. It is hoped that by utilizing the Kahoot application it will be able to attract the attention of students in learning. The use of Digital Game Based Learning-based learning media is highly recommended for teachers to apply it in their respective schools because after conducting research it is very visible that students are very enthusiastic in carrying out learning because in delivering learning material the teacher applies it using games or quizzes. Therefore it can be concluded that implementing TPACK learning by utilizing this kahoot application and developing it using Digital Game Based Learning learning media is able to increase students' attention in carrying out learning.